ANALYSIS OF OIL ABSORPTION AND FRICTION COEFFICIENT OF BAMBOO POWDER, COCONUT POWDER, GLASS POWDER, AND COPPER POWDER COMPOSITES FOR CLUTCH PADS - Iqbal Risyuma; Muhamad Fitri (Universitas Mercu Buana, 2022)
This study aims to determine the characteristics of the absorption test with SAE 10W-30 and the friction coefficient test with the ASTM D 3702-94 test standard on composite clutch pads made from bamboo powder, coconut powder, glass powder, and copper powder. It is based on the considerations that there are abundance of natural resources of bamboo and coconut with that is still not optimally utilized as well as the discovery of several hazardous clutch lining (asbestos) basic material properties. In each test, each composition variation was tested 3 times and from the data, the average value of the composition variation was taken. Based on this research, the specimen with the highest oil absorption value is specimen combination 3 (BB20KL20CU0KC20) with an absorption value of 17.98% and the specimen with the lowest absorption value is specimen combination 2 (BB20KL20CU5KC15) with an absorption value of 4.88%, and the specimen with the highest percentage change in volume is specimen combination 1 (BB20KL20CU10KC10) with a percentage of 3.30%, and the specimen with the lowest percentage change in volume is specimen combination 2 (BB20KL20CU5KC15) with a percentage of 1.01%. From the results of the combined friction coefficient test, specimen 3 (BB20KL20CU0KC20) has the highest friction coefficient value of 0.54526 and specimen 2 (BB20KL20CU5KC15) has the lowest friction coefficient value of 0.16923.